Outlet AKH, Produk Khas Madura - Dwi Ivayana Sari; Miariza Wanti; Masluha (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
The Covid-19 pandemic in Indonesia has had a major impact in various fields, especially the economy. Based on the results of observations of producers of typical Madurese products spread across four regencies on the island of Madura (Bangkalan, Sampang, Pamekasan and Sumenep) it shows that in mid-2020 the demand for distribution of Madurese products has decreased, retail sales have decreased significantly. This service program is carried out with the main aim of making the economic wheels of the Madurese community turn again. The implementation of the program consists of 4 stages, namely the pre-production stage, the production stage, the marketing stage and the marketing evaluation. The results of the implementation of this program are able to create new AKH outlets that can be accessed by everyone. This is because within 3 months, apart from coming from Bangkalan, AKH outlet consumers also come from outside Bangkalan, (2) Marketing strategies (offline and online) are able to move the economy of the Madurese community in the midst of the Covid-19 pandemic, (3) Packaging that has been created very attractive and in accordance with the development of the millennial era.